Pengaruh Core Stability Exercise Terhadap Keseimbangan Statis Anak Usia 7-9 Tahun Di SD Tanwir Surabaya - Nur Aini; Nurul Halimah; Rachma Putri Kasimbara; Agung Hadi Endaryanto (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Balance is how the position of the body is able to maintain and adjust the position while still or moving. Good balance will increase body awarenes and related to spatial and reasoning ability. Core Stability Exercise is called an exercise that involves the trunk whose function is to control motion and position with the aim of making optimal movements, based on the physiological side, the strengthening and stability of the torso increases the strength and power and efficient movement of the shoulder, arm and leg muscles. The muscles in our body work like a chain, so that when movement occurs in the limbs, the core muscles will keep our body in an upright position.